ICT-Mediated Kaiwa Learning for Intercultural Communication: A Literature Review - Sonda Sanjaya (Chi e Journal of Japanese Learning and Teaching, 2026)
As Japanese is increasingly used a medium of communication among non-native speakers, often referred to as Japanese as a Lingua Franca (JLF), Japanese language education must respond to the growing need for both linguistic and intercultural competence. This is particularly relevant in Southeast Asian contexts, including Indonesia, Vietnam, Thailand, and the Philippines, where Japanese is learned as a foreign language rather than used as an official language. This article presents a literature review of ICT-based kaiwa (conversation) learning in intercultural exchange settings. By examining previous studies on telecollaboration and other forms of ICT-mediated interaction, the review identifies the pedagogical potential of combining synchronous web conferencing with asynchronous digital platforms. The findings suggest that such practices can strengthen learner motivation, foster cultural awareness, and support the negotiation of meaning in intercultural communication. Moreover, ICT enables authentic interactional opportunities that transcend geographical limitations. These findings offer an important basis for designing Japanese language instruction that integrates intercultural understanding and promotes more effective communication among learners in Southeast Asia.